Decision tree for local + global imperfection combinations in double-symmetric prismatic members – Practical recommendations in the framework of advanced analysis - Müller, Andreas; Vild, Martin; Taras, Andreas (Ernst & Sohn, 2023)
Better and simpler possibilities of structural optimization due to increasing computational power but also for reasons of environmental sustainability, the use of materials and their reusability lead to greater acceptance towards more advanced numerically intensive, so-called ‘design by analysis' methods like geometrically and materially non-linear analyses with imperfections (GMNIA). The general choice of imperfections and their combination in such models, especially for slender cross sections of intermediate length prone to an interaction between a global and local plate buckling, is crucial in terms of the reached load-bearing capacity. Annex C of EN 1993-1-5:2010 makes use of the ‘70 %-rule' for the combination of imperfection modes and amplitudes. This rule postulates that two GMNIA calculations should be conducted when local and global interactive buckling may be dominant; one with 100 % + 70 % of the maximum specified amplitude in either case. In addition, extended information is provided on the choice and combination of imperfections in the newly introduced and currently available draft of the prEN 1993-1-14:2020 (design assisted by finite element analysis). Although information is provided on how the local and global imperfections should be combined, it is not stated when it is relevant to consider those. Based on conducted GMNIA simulations on SHS/RHS (square and rectangular hollow sections) and I-shaped sections, this article presents general decision support on the choice of equivalent imperfections. On the basis of numerical analysis, the developed flow chart and design routine allow for the decision whether the consideration of the interaction of local and global imperfections is required or not.

Better and simpler possibilities of structural optimization due to increasing computational power but also for reasons of environmental sustainability, the use of materials and their reusability lead to greater acceptance towards more advanced numerically intensive, so-called ‘design by analysis' methods like geometrically and materially non-linear analyses with imperfections (GMNIA). The general choice of imperfections and their combination in such models, especially for slender cross sections of intermediate length prone to an interaction between a global and local plate buckling, is crucial in terms of the reached load-bearing capacity. Annex C of EN 1993-1-5:2010 makes use of the ‘70 %-rule' for the combination of imperfection modes and amplitudes. This rule postulates that two GMNIA calculations should be conducted when local and global interactive buckling may be dominant; one with 100 % + 70 % of the maximum specified amplitude in either case. In addition, extended information is provided on the choice and combination of imperfections in the newly introduced and currently available draft of the prEN 1993-1-14:2020 (design assisted by finite element analysis). Although information is provided on how the local and global imperfections should be combined, it is not stated when it is relevant to consider those. Based on conducted GMNIA simulations on SHS/RHS (square and rectangular hollow sections) and I-shaped sections, this article presents general decision support on the choice of equivalent imperfections. On the basis of numerical analysis, the developed flow chart and design routine allow for the decision whether the consideration of the interaction of local and global imperfections is required or not.
Decision tree for local + global imperfection combinations in double-symmetric prismatic members – Practical recommendations in the framework of advanced analysis
Keywords: LBA simulations; GMNIA simulations; advanced non-linear analysis; equivalent imperfections; combination of local and global imperfections; LBA simulations; GMNIA simulations; advanced non-linear analysis; equivalent imperfections; combination of local and global imperfections